Search for the rare decay B0 → J/ψϕ*Individual groups or members have received support from AvH Foundation (Germany); EPLANET, Marie Sk lodowska-Curie Actions and ERC (European Union); A*MIDEX, ANR, Labex P2IO and OCEVU, and R´egion Auvergne-Rhˆone-Alpes (France); Key Research Program of Frontier Sciences of CAS, CAS PIFI, Thousand Talents Program, and Sci. & Tech. Program of Guangzhou (China); RFBR, RSF and Yandex LLC (Russia); GVA, XuntaGal and GENCAT (Spain); the Royal Society and the Leverhulme Trust (United Kingdom). (April 2021) - Aaij, R.; Abellán Beteta, C.; Ackernley, T.; Adeva, B.; Adinolfi, M.; Afsharnia, H.; Aidala, C.A.; Aiola, S.; Ajaltouni, Z.; Akar, S.; Albrecht, J.; Alessio, F.; et al.
Abstract: A search for the rare decay is performed using collision data collected with the LHCb dete-ctor at centre-of-mass energies of 7, 8 and 13 TeV, corresponding to an integrated luminosity of 9 fb −1 . No significant signal of the decay is observed and an upper limit of at 90% confidence level is set on the branching fraction.